Photocatalytic Hydrogen Production over Ni/La-NaTaO3 Nanoparticles from NaCl-water Solution in the Presence of Glucose as Electron Donor - Husni Husin; Komala Pontas; Yunardi Yunardi; Adi Salamun; Pocut Nurul Alam; Fikri Hasfita (ASEAN Journal of Chemical Engineering, 2018)
Nanoparticles La-NaTaO3 photocatalyst has been synthesized via a sol-gel route. A Ninanoparticle (NPs) as a cocatalyst is loaded on La-NaTaO3 by a simple impregnation method.The products are characterized by X-ray diffraction (XRD), scanning electron microscope(SEM), a high-resolution transmission electron microscope (HRTEM) and X-ray photoelectronspectroscopy (XPS). X-ray diffraction of the La-NaTaO3 samples shows perovskite-typecrystalline orthorhombic structure. Small particulate solids of La-NaTaO3 (30-250 nm) areobserved by SEM measurement. The nickel particles are detected from HRTEM images isaround 4-8 nm. The hydrogen evolution over La-NaTaO3 with NaCl is much higher than thatwithout NaCl. The photoactivity of La-NaTaO3 is enhanced when Ni is loaded on the surfaceof La-NaTaO3. The optimum loading amount of nickel is found to be 0.3 wt.% for La-NaTaO3,and it is more effective for H2 production from NaCl-water solution in the presence glucose.It is revealed that the loaded Ni can interact with each other and cooperate on improving thephotocatalytic activity. In the case of glucose as an electron donor, the activity ofphotocatalytic hydrogen generation over Ni/La-NaTaO3 increases dramatically. NaCl andglucose can promote markedly the photocatalytic hydrogen evolution. The Ni/La-NaTaO3nanoparticles system appears to be a promising candidate, which is very important to practicalapplications, including the production of H2 from NaCl-water solution in the presence ofglucose.